ALGORITMA FLOYD WARSHALL UNTUK MENENTUKAN JALUR TERPENDEK EVAKUASI TSUNAMI DI KELURAHAN SANUR - SANI, AJENG FITRAH; TASTRAWATI, NI KETUT TARI; DWIPAYANA, I MADE EKA (E-Jurnal Matematika, 2013)
Sanur village is one of beautiful tourism spots in Bali. Sanur is located in south of Bali, Indonesia. There are many beaches in that place. Besides of beautifulness of it, Sanur potentially to be attacked by Tsunami disaster because of it is location  near subduction Zone. It is important to know Tsunami evacuation track. This research tries to give alternative Tsunami evacuation track by using Floyd Warshall algorithm. The result of this research is Tsunami evacuation track in sanur by using Floyd Warshall algotihm
Keywords: Floyd Warshall; Dynamic Programming; Jalur Terpendek; Evakuasi; Tsunami